Grid-connected Electricity Generation Potential from Energy Crops: A Case Study of Marginal Land in Thailand - Pratumwan, Thanarat; Tia, Warunee; Nathakaranakule, Adisak; Soponronnarit, Somchart (International Journal of Energy Economics and Policy, 2022)
This paper provides an assessment of the geographical potential of grid-connected electricity generation from the planting of energy crops using GIS while also estimating the levelized costs of electricity (LCOE) under three biomass-prices scenarios. To avoid competition for land use between food and energy crops, marginal land or unsuitable areas (low soil fertility) were used as case study sites for planting energy crops (Napier grass). The total estimated potential based on the location of energy crops and electrical substations was 11,224 MW or 66,367 GWh/y, equivalent to approximately 26.5% of Thailand's total electricity demand in 2037. The LCOEs under the three scenarios ranged from 0.103 to 0.120 USD/kWh for a 9MW capacity power plant, which were lower than the feed-in tariff rate. The results of economic assessment under three scenarios showed positive NPV values but relatively long discounted payback periods. The project and equity IRR ranged from 11.94 to 14.04% and 24.40 to 30.89%, respectively. These findings can be used for land-use planning and energy crop promotion to increase the share of grid-power generation from biomass.